Klaus Holzkamp (1927-1995) e a psicologia crítica alemã: introdução à proposta de uma ciência marxista do sujeito - Cruvinel, Lucas Matheus Pereira (2021)
Klaus Holzkamp (1927-1995) was a psychologist and university professor who played an important role in the development of German Critical Psychology (PCA), which was extremely appropriate for Brazilian Psychology. His theory was developed in the Federal Republic of Germany in the context of the Cold War. With investigations initially in the field of constructionism, the author appropriated Marxism from his involvement with the student movements that gained strength during the 1960s. With this approach, Holzkamp rejected his previous production and made a positive criticism from what had taken place in psychology. In this sense, we aim to appropriate the later phase of his work. More specifically, we seek to (a) identify the relationship between his production and the historical and social moment in which it was created; (b) understand the theoretical inflections operated throughout his work; and (c) appropriating his writings from 1983 onwards. This cut is due to the difficulty of accessing his works in languages other than German. It is concluded that the PCA is an important expression of Critical Psychology worldwide, the result of an approach to Marxism at a time of heightened social struggles. This perspective has several contributions to Brazilian Psychology, both because of the possible similarities with Latin American theoretical movements, and because of its explanatory capacity as a result of a critical rescue of the knowledge produced so far